Identifying remote sources of interannual variability for summer precipitation over Nordic European countries tied to global teleconnection wave patterns. Issue 1 (1st January 2020) - Fuentes-Franco, Ramón; Koenigk, Torben
Abstract: We show evidence that tropical atmospheric variability over the central tropical Pacific modulates the circulation over the western Arctic and the North Atlantic-European sector, impacting the summer precipitation especially over Nordic European countries (NEC). Our results, based on the ERA5 reanalysis, suggest the occurrence of a teleconnection mechanism (similar to the Pacific North American pattern) between the tropical Pacific in early spring and summer precipitation over NEC, and we propose two indices as predictors for NEC summer precipitation based on geopotential height anomalies at 500 hPa over the western tropical Pacific during March. We propose an empirical model based on both indices as predictors and assess the model's skill with a leave-one-out cross-validation procedure. Over large portions of NEC, our proposed empirical model is able to reproduce dry, normal and wet years, defined from summer standardized precipitation anomalies, with a Heidke skill score greater than 0.9.